Death with dignity. Issue 4 (1st August 2002) - Allmark, Peter
Abstract : The purpose of this article is to develop a conception of death with dignity and to examine whether it is vulnerable to the sort of criticisms that have been made of other conceptions. In this conception "death" is taken to apply to the process of dying; "dignity" is taken to be something that attaches to people because of their personal qualities. In particular, someone lives with dignity if they live well (in accordance with reason, as Aristotle would see it). It follows that health care professionals cannot confer on patients either dignity or death with dignity. They can, however, attempt to ensure that the patient dies without indignity. Indignities are affronts to human dignity, and include such things as serious pain and the exclusion of patients from involvement in decisions about their lives and deaths. This fairly modest conception of death with dignity avoids the traps of being overly subjective or of viewing the sick and helpless as "undignified".